(untitled) (Revista INTEREDU11, 2024)
School engagement is relevant to students’ academic, success and performance. One factor that affects this is academic self-concept. However, how the two interact is not entirely clear. Therefore, the objective of this study was to determine the process by which academic self-concept influences school engagement. For this, the factors of academic self-efficacy and academic performance, from academic self-concept, and of cognitive engagement and emotional engagement, from school engagement, were included. These were measured in second cycle basic students of an educational establishment in Gran Concepción. The relationships between these were evaluated using linear regression models. The results showed that they maintain a positive association. Specifically, between academic self-efficacy and cognitive engagement. From this, the implication of these results for school life and future lines of research are discussed.